Classroom Management in Language Education - Wright, T. author. aut Link
XI, 497 p.
Keywords: A book that develops an understanding of practices at the very centre of language education - the classroom. It is written for postgraduate students in Applied Linguistics and Education, and practitioners, whether in TESOL or other language teaching, In Part 1 the author explores key concepts in unpacking the complexity of classroom life. In Part 2 existing research and practice are examined through a series of research case studies. Part 3 provides a template for research activity and suggestions for projects and methodologies, and Part 4 collects resources for readers keen to follow up the themes developed in the book.